2021
DOI: 10.1126/scisignal.abb1953
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-independent activity of the ghrelin receptor modulates AMPA receptor trafficking and supports memory formation

Abstract: The biological signals of hunger, satiety, and memory are interconnected. The role of the hormone ghrelin in regulating feeding and memory makes ghrelin receptors attractive targets for associated disorders. We investigated the effects of the high ligand-independent activity of the ghrelin receptor GHS-R1a on the physiology of excitatory synapses in the hippocampus. Blocking this activity produced a decrease in the synaptic content of AMPA receptors in hippocampal neurons and a reduction in GluA1 phosphorylati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…We have shown that ghrelin-dependent and ghrelin-independent activities of GHSR impair native presynaptic Ca V 2.2 currents and reduce GABA release from hypothalamic and hippocampal neurons ( Cabral et al, 2014 ; Lopez Soto et al, 2015 ; Martinez Damonte et al, 2018 ). Such presynaptic effects of GHSR result in disinhibition of post-synaptic neurons and contribute to enhance GHSR mediated neuronal activation due to other molecular mechanisms, such as neuronal depolarization induced by ghrelin-mediated inhibition of voltage-gated potassium channels ( Shi et al, 2013 ) and ghrelin-dependent and ghrelin-independent increase of AMPA receptor trafficking in hippocampal neurons ( Ribeiro et al, 2014 ; Ribeiro et al, 2021 ). LEAP2 inhibition of GHSR activity converts this peptide into a putative important player in the control of neuronal plasticity and excitability.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that ghrelin-dependent and ghrelin-independent activities of GHSR impair native presynaptic Ca V 2.2 currents and reduce GABA release from hypothalamic and hippocampal neurons ( Cabral et al, 2014 ; Lopez Soto et al, 2015 ; Martinez Damonte et al, 2018 ). Such presynaptic effects of GHSR result in disinhibition of post-synaptic neurons and contribute to enhance GHSR mediated neuronal activation due to other molecular mechanisms, such as neuronal depolarization induced by ghrelin-mediated inhibition of voltage-gated potassium channels ( Shi et al, 2013 ) and ghrelin-dependent and ghrelin-independent increase of AMPA receptor trafficking in hippocampal neurons ( Ribeiro et al, 2014 ; Ribeiro et al, 2021 ). LEAP2 inhibition of GHSR activity converts this peptide into a putative important player in the control of neuronal plasticity and excitability.…”
Section: Discussionmentioning
confidence: 99%
“…With the key role ghrelin has with regards to homeostatic feeding and glucose metabolism (Tschop et al, 2000 ; Gray et al, 2019 ), metabolic changes and weight less is to be expected from such a treatment. Beyond ghrelin's traditional role, a recent study showed that the intrinsic activity of GHSR-1A is important for AMPA receptor trafficking and memory formation (Ribeiro et al, 2021 ). Consequently, an inverse agonist of GHSR-1A, such as PF-5190457, may cause cognitive deficits associated with learning.…”
Section: Appetite-regulatory Peptides In Substance Use Disordermentioning
confidence: 99%
“…Recently, more and more data have appeared on the so‐called ligand‐independent activity of GHS‐R1a, that is, about the active conformational state of the receptor in the absence of ligands. It is assumed that this activity is important for many physiological processes (Ribeiro et al, 2021 ).…”
Section: Ghs‐r1a In the Brainmentioning
confidence: 99%